«Intermittent» adenomegaly: a clinical case in general practice (Portuguese Journal of Family Medicine and General Practice, 2018)
Introduction: Adenomegaly is a frequent finding during physical examination, and it is important for the general practitioner to identify those that may be suspicious, and make a timely referral. This case shows an unpredictable manifestation of adenomegalies of suspicious characteristics, which appear and regress spontaneously over the years. With this case report we wish to draw attention to the need to always value suspicious adenomegalies, and also to elucidate on the diagnostic approach to these manifestations.Case study: 69-year-old woman, with a history of lymph node tuberculosis in 2008, treated with tuberculostatic drugs for nine months. In 2014, following the identification of new cervical and supraclavicular adenomegalies of suspicious characteristics on the right, a new clinical investigation was performed, but the results were inconclusive given the spontaneous remission of the condition. Two years later, the patient returns showing supraclavicular adenomegalies on the left, which were further investigated by fine-needle aspiration cytology, showing the presence of neoplastic cells. The patient was referred to general surgery for excisional biopsy of the lymph node, which established the diagnosis of non-Hodgkin’s follicular lymphoma. Chemo-therapy was therefore initiated at the Portuguese Institute of Oncology (IPO), with good tolerance and response.Comment: Follicular lymphoma is an indolent condition and may present as adenomegalies that appear and regress spontaneously during the course of several years, an unpredictable characteristic that hinders the diagnosis. However, the continuity of care characteristic of general practice facilitates the detection of the recurrence of the disease, and allows it timely referral.
Keywords: Lymphadenopathy; Non-Hodgkin’s follicular lymphoma.